2022
DOI: 10.3389/fonc.2022.1084683
|View full text |Cite
|
Sign up to set email alerts
|

The adverse impact of a gain in chromosome 1q on the prognosis of multiple myeloma treated with bortezomib-based regimens: A retrospective single-center study in China

Abstract: BackgroundMultiple myeloma is genetically heterogeneous, and chromosome abnormalities play a pivotal role in prognosis. A gain in chromosome 1q (+1q) is among the most common cytogenetic abnormalities; however, its relationship with overall survival (OS) and progression-free survival (PFS) in patients with multiple myeloma is still unclear. We aim to clarify the impact of +1q on the clinical characteristics and survival outcomes of patients treated with bortezomib-based combination regimes.Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…A previous study showed that the MYC chromosomal copy number was related to the clinical response to paclitaxel and the in vitro antitumor effect of mTORC1/2 inhibition [ 33 ]. Another retrospective study showed that chromosomal 1q gain may have a detrimental impact on the prognosis of multiple myeloma when treated with bortezomib-based regimens [ 34 ]. However, that study included only one exceptional responder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the MYC chromosomal copy number was related to the clinical response to paclitaxel and the in vitro antitumor effect of mTORC1/2 inhibition [ 33 ]. Another retrospective study showed that chromosomal 1q gain may have a detrimental impact on the prognosis of multiple myeloma when treated with bortezomib-based regimens [ 34 ]. However, that study included only one exceptional responder.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, chromosomal 1q gain and whole chromosome 6 loss were detected in advanced thymomas. In other tumors, chromosome 1q gain was identified in multiple myeloma [ 34 , 40 ], ependymoma [ 41 ], Wilms tumor [ 42 ], and New Zealand virus-negative Merkel cell carcinomas [ 43 ]. Whole chromosome 6 loss has been detected in acute lymphoblastic lymphoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ixazomib preferentially binds to the 20S proteasome β5 subunit to inhibit chymotrypsin-like activity (114). A summary of studies on IMiDs and PIs in NDMM patients with 1q21 + over the past 3 years is presented in Table III (81,(117)(118)(119)(120)(121). In a previous study, patients with 1q21 gain receiving bortezomib-based treatment had significantly improved the OS and PFS when compared with non-bortezomib treatment (3-year PFS, 62.8 vs. 8.75%; P=0.0385; 3-year OS, 82.3 vs. 18.8%; P=0.0154) (81).…”
Section: Treatment Of MM Patients With 1q21 +mentioning
confidence: 99%